Nondestructive Detection of Frankia in Alnus glutinosa With NIR Spectroscopy - Georgopoulos, Konstantinos; Bezemer, T. Martijn; Vesterdal, Lars; Li, Kaiyi; Nobel, Léon; Gomes, Sofia I. F. (Plant-environment interactions (Hoboken, N.J. : 2018), 2025)
ABSTRACT Nitrogen (N) is essential for plant growth, yet excessive fertilizer use contributes to environmental degradation. Actinorhizal trees like Alnus glutinosa form symbiotic relationships with nitrogen‐fixing bacteria of the genus Frankia, reducing reliance on synthetic fertilizers. However, distinguishing between soil‐derived and symbiotically fixed nitrogen remains a challenge. This study investigates the potential of NIR spectroscopy as a nondestructive tool for differentiating N sources in A. glutinosa. Seedlings were grown in sterilized soil under controlled conditions with and without Frankia inoculation, and across a gradient of NH4NO3 fertilization (0–20 mM). We measured leaf chlorophyll, nitrogen content, biomass, and NIR reflectance (330–1100 nm) of the third fully expanded leaf. principal component analysis (PCA) and partial least squares (PLS) regression revealed that spectral signatures significantly differed between inoculated and uninoculated plants, particularly in the visible range around 555 nm. Despite similar leaf chlorophyll levels, Frankia‐inoculated plants and those fertilized with 20 mM NH4NO3 exhibited spectral differences that could otherwise not be detected by SPAD measurements. PLS regression explained up to 54.8% of spectral variance based on nitrogen source, even in the absence of unique spectral peaks. These findings highlight the potential of NIR spectroscopy for rapid, in vivo and in vitro assessment of symbiotic N‐fixation in trees, offering a novel and more precise approach than SPAD measurements.